Eating Disorder Inventory-3, validation in Swedish patients with eating disorders, psychiatric outpatients and a normal control sample. (February 2015) - Nyman-Carlsson, Erika; Engström, Ingemar; Norring, Claes; Nevonen, Lauri
Abstract Background: The Eating Disorder Inventory-3 (EDI-3) is designed to assess eating disorder psychopathology and the associated psychological symptoms. The instrument has been revised and has not yet been validated for Swedish conditions in its current form. Aims: The aim of this study was to investigate the validity and reliability of this inventory and present national norms for Swedish females. Methods: Data from patients with eating disorders (n = 292), psychiatric outpatients (n = 140) and normal controls (n = 648), all females, were used to study the internal consistency, the discriminative ability, and the sensitivity and specificity of the inventory using preliminary cut-offs for each subscale and diagnosis separately. Swedish norms were compared with those from Denmark, USA, Canada, Europe and Australian samples. Results: The reliability was acceptable for all subscales except Asceticism among normal controls. Analysis of variance showed that the EDI-3 discriminates significantly between eating disorders and normal controls. Anorexia nervosa was significantly discriminated from bulimia nervosa and eating disorder not otherwise specified on the Eating Disorder Risk Scales. Swedish patients scored significantly lower than patients from other countries on the majority of the subscales. Drive for Thinness is the second best predictor for an eating disorder. The best predictor for anorexia nervosa was Interoceptive Deficits and Bulimia for the other diagnoses. Conclusions/clinical implications: The EDI-3 is valid for use with Swedish patients as a clinical assessment tool for the treatment planning and evaluation of patients with eating-related problems. However, it still exist some uncertainty regarding its use as a screening tool.